THE IMPORTANCE OF TEACHING TECHNOLOGY BASED ON FOREIGN EXPERIENCES (Open Academia: Journal of Scholarly Research, 2024)
In today’s fast-paced and technology-driven world, the need for effective technology education has never been more crucial. Teaching technology based on foreign experiences provides valuable insights into how different countries approach the integration of technology in education. By examining international best practices, educators can adopt innovative methods and enhance the quality of technology education. This article explores the importance of teaching technology through global experiences, focusing on key strategies such as project-based learning, interdisciplinary approaches, the use of digital and online platforms, and the emphasis on innovation. Moreover, it discusses how these methods prepare students to thrive in a technology-driven, global economy. Ultimately, the adoption of foreign experiences in technology education can help improve educational systems and foster a competitive and skilled workforce